Prostate seed implantation robot - ZHANG MINGCHEN; CHANG QING; QIAO ZHIXIA (2018)
The invention discloses a prostate seed implantation robot. The robot comprises a base, a robot body and an end effector fixed to the tail end of the robot; the end effector mainly comprises a medicalultrasonic probe, a seed implantation needle and a guide sleeve adjusting mechanism capable of controlling implantation needle puncture location and angle; the medical ultrasonic probe can be conveniently assembled and disassembled on the end effector through a pressing plate and a buckle and can enter the rectum of a patient through the anus of the patient under the drive of the robot so as to obtain an ultrasonic image of the prostate, and the end effector can rotate around the center line of the medical ultrasonic probe and move horizontally along the center line; a guide sleeve in the guide sleeve adjusting mechanism can adjust the angle and can horizontally move along an adjusting support vertically, and the end effector rotates around the center line of the medical ultrasonic probeand horizontally moves alo